Monitoring Tuberculosis Patient: the Effectiveness of Directly Observed Therapy (DOT) or PMO - Ni Made Ernita Refayanti; Ni Made Novi Purnami; Meuthia Faralita Annisa (GLOBAL HEALTH SCIENCE GROUP, 2026)
Although global incidence and mortality rates of tuberculosis (TB) have declined, TB remains the second leading cause of death worldwide after HIV/AIDS. To improve treatment adherence, the World Health Organization (WHO) recommends the Directly Observed Treatment, (DOT) strategy, known in Indonesian as the Pengawas Minum Obat (PMO). PMOs are expected to support, remind, and motivate patients to complete their treatment regimen effectively. This study aimed to determine the prevalence of PMO use, identify PMO characteristics, assess medication adherence among active TB patients, and evaluate the relationship between PMO presence and adherence. A descriptive–analytic study with a cross-sectional design using total sampling of all TB patients who were actively undergoing treatment at the Sigerongan Primary Health Care. Data were collected through structured interviews and analyzed using the chi-square statistical test. The study found no significant difference in medication adherence between patients with a PMO and those without (p = 1.000; p > 0.05). Interestingly, 21.7% of patients with a PMO were still non-adherent to their treatment. The study found no significant difference in medication adherence between patients with a PMO and those without. This may be influenced by the small sample size and suboptimal role execution of PMOs.